Patients With Epileptic Seizures and Multiple Sclerosis in a Multiple Sclerosis Center in Southern Germany Between 2003–2015 - Schorner, Anja; Weissert, Robert (Frontiers in Neurology, 2019)
Background: So far, many studies have shown that the risk of developing seizures and epilepsy is higher among patients with multiple sclerosis (MS) than in the general population. However, the causal link between these two diseases is still unclear. In addition, it is not clearly understood whether and to what extent the manifestation of seizures and epilepsy in patients with MS affects the clinical course and the long-term prognosis of the disease. We aimed to retrospectively identify and describe patients with MS and with seizures and epilepsy which were seen at the Department of Neurology of the University of Regensburg in Germany between the years 2003 and 2015. Methods: With the help of the electronic documentation system of hospital admitted patients followed by scrutinizing medical records of patients with MS for evidence of seizures and epilepsy, we identified patients with MS and seizures or epilepsy. Results: We identified 22 individuals (1.74%) out of 1267 patients with MS with seizures or epilepsy. 18 of these 22 individuals met criteria for epilepsy (1.42%). Nine MS patients (40.9%) suffered from relapsing-remitting MS (RRMS) whereas eleven MS patients (50.0%) showed a secondary progressive disease course (SPMS). Five of those (45.5%) converted from RRMS to SPMS before they acquired epilepsy. None of the identified patients with MS and seizures or epilepsy suffered from primary progressive MS (PPMS). Moreover, two MS patients (9.1%) had a history of seizures before MS onset. Seizures were of focal onset in 17 patients with MS (77.3%). 14 out of these 17 MS patients presented with focal to bilateral tonic-clonic seizures (82.4%). Five MS patients (22.7%) showed tonic clonic seizures of unknown onset. Status epilepticus was reported in three patients with MS (13%), for one patient, the data was inconclusive. Conclusion: The occurrence of seizures and epilepsy was higher than in the general population, suggesting a causal relationship between both diseases. In most cases, seizures occurred after the first manifestation of MS. The high frequency of focal seizures supports the concept of cerebral lesions in patients with MS playing an important role in precipitation of seizures and epilepsy.